50.1k views
0 votes
Need answer 10 points

Need answer 10 points-example-1
User Srivatsan
by
4.6k points

2 Answers

5 votes

Answer:

B

Explanation:

√x + 6 = x

x - √x - 6 = 0

(√x - 3)(√x + 2) = 0

so

√x = -2 (impossible)

or

√x = 3 => x = 9

User JeffreyABecker
by
5.0k points
4 votes

√x + 6 = x

Well the solution to the equation would be B because x=9.

Therefore your answer is 9.

User Tikhon
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.